A comparative study on proximate composition of fresh and salt-boiled prawn (Macrobrachium rosenbergii) frozen stored at -20oC - Mukta, Shabnam Yasmin; Masum, Shamsuzzaman; Naher, Jasmin; Chakraborty, Suvash Chandra; Mansur, Md Abul (Research in Agriculture Livestock and Fisheries, 2016)
A study was conducted to evaluate the proximate composition of fresh and salt-boiled prawn stored at -200 C. The study was focused on comparative study on proximate composition, nutritional status and quality of the prawn in wet matter basis. The collected fresh prawns were boiled in 2.5% brine for 15 minutes followed by freezing at -200 C to evaluate the quality of prawns at 16 weeks period of frozen storage. The sample was stored separately in individual boxes for every experimental uses. The proximate composition of the sample during frozen storage (16 weeks) was evaluated by studying organoleptic assessments, protein, lipid, ash, moisture and TVBN. The fresh prawn during frozen storage was organoleptically accepted up to 12 weeks but unaccepted after 16 weeks of storage whereas the salt-boiled frozen prawn was remained acceptable after 16 weeks of frozen storage at -200C. The initial protein content of fresh prawn was decreased gradually with the storage period. At the end of the 16 weeks of frozen storage, initial protein content of fresh prawn was decreased from 22.36 ±0.45% to 16.24 ±0.27% and protein content of salt-boiled prawn was decreased from 29.69 ±0.28% to 22.89 ±0.29%. The initial lipidcontent of fresh prawn decreased gradually with the storage period and at the end of the 16 weeks frozen storage it decreased from 2.4±0.16% to 1.24 ±0.13% and for the salt-boiled frozen prawn it decreased from2.56 ±0.11% to 1.68 ±0.26%. The initial ash content of fresh prawn decreased gradually with the storage period and at the end of the 16 weeks frozen storage, it decreased from 2.42±0.21% to 1.52±0.23%, whereas for salt-boiled prawn it decreased from2.89 ±0.19% to 1.93 ±0.18%.The initial TVB-N content increased gradually with the storage period and at the end of the 16 weeks of frozen storage it increased from 10.23±0.26 mg/100g to 32.01±1.36 mg/100g in fresh frozen prawn, where in the salt-boiled prawn, it was increased from 8.35 ±0.28 mg/100g to16.82 ±1.09mg/100g. From the findings it can be concluded that, the quality & nutritional composition of the salt-boiled prawn remains better than that of fresh un-boiled one during long storage period. So, the process for frozen storage of salt-boiled prawn at -200 C can be considered as a new approach in fish preservation. Res. Agric., Livest. Fish.3(1): 241-250, April 2016